Effectiveness and Predictors of Response to 1-Hz Repetitive Transcranial Magnetic Stimulation in Patients With Obsessive-Compulsive Disorder. Issue 1 (March 2019) - Singh, Swarndeep; Kumar, Saurabh; Gupta, Ankit; Verma, Rohit; Kumar, Nand
Abstract : Objective: The present study aimed to assess the effectiveness of repetitive transcranial magnetic stimulation (rTMS) treatment targeting either supplementary motor area (SMA) or orbitofrontal cortex (OFC) among patients with OCD in real-world clinical practice settings. Also, the present study explored for potential predictors of response to rTMS treatment. Methods: Retrospective review and analysis of records of 79 patients with medication-refractory OCD, all of whom had received 20 sessions of 1-Hz rTMS as part of routine clinical care. Of 79 patients, 46 received rTMS over the bilateral SMA and 33 over the left OFC. A reduction of 25% and 35% in Yale-Brown Obsessive Compulsive Scale (YBOCS) scores was used to classify outcome as partial and complete response, respectively. Statistical analysis was done using SPSS version 23.0. Results: There was a significant decrease in mean YBOCS score from baseline to end of treatment (7.68 ± 5.62; t = 12.14, P < 0.001). Forty-five patients (57%) met criteria for partial response, of which 32 patients (40.5%) showed complete response. There was no significant difference in outcomes between patients receiving rTMS over SMA or OFC. Binary logistic regression analysis revealed presence of comorbid depression and higher baseline YBOCS score to be associated with lesser likelihood of response to rTMS. Conclusions: This study provided evidence for overall effectiveness of adjunctive 1-Hz rTMS treatment over either SMA or OFC in patients with medication-refractory OCD, and reported comorbid depression and higher pretreatment YBOCS scores as potential predictors of poor response to rTMS.